Pseudomonas aeruginosa: distribution and antibiotic profile of one of the ESKAPE pathogen - Karthick, Mowna (Tropical Journal of Pathology and Microbiology, 2019)
Background: Pseudomonas aeruginosa is an opportunistic gram-negative pathogen known for its ingenious mode of infection. The management of infections with Pseudomonas has been quite a challenge. The bacteria have intrinsic resistance against most of the routine antibiotics. Such a scenario places the health care delivery system at a challenging end point with very minimal options of care and increased rates of morbidity and mortality. This study was done to assess the pattern of presentation of Pseudomonas aeruginosa in hospital settings. Methods: This cross-sectional study was carried out among 280 specimens which were isolated for a period of 17 months in our tertiary care hospital. The blood culture bottles were placed in Bac T/ Alert 3 D and the positive culture bottle was processed by Grams stain and in routine bacteriological media for inoculation and incubated. Pseudomonas aeruginosa organisms isolated from all the clinical samples were subjected for determining the identification and antibiotic susceptibility profile by VITEK 2 and manual methods. Results: A total of 280 samples were analyzed in this study. The background characteristics of the specimens analyzed is given in table 1. In this study, majority of the samples were from inpatients (71.4%). Among the total samples, most specimens were urine samples (37.5%), followed by pus (23.1%). The organisms showed high sensitivity to Amikacin, Ceftazidime and Gentamycin (98%). Conclusion: From the present findings, we understand that Amikacin and Gentamycin can be the proposed drug of choice for severe infections with Pseudomonas aeruginosa.